Adopting Digital Technology in Teaching and Learning Environment in Early Childhood Education Classes in Nairobi County, Kenya (Asian Education Studies, 2017)
Dispositions towards use of digital technologies in modern early childhood settings have dramatically transformed aspects in education sector through development and integration of technology into education policy, curriculum and practice. Digital technology as a tool in instruction benefits learner’s fine motor skills, language and communication readiness, mathematical thinking as well as positive attitudes towards learning. Conversely inadequate educational and digital competence hampers teachers in Early Childhood Education (ECE) access to digital technology. This study assessed ways in which teachers in ECE in Kenya access digital technologies. It was designed as a two-phase exploratory mixed methods study. The design allowed collection of data from two groups of ECE educators: case study and survey teachers. Case-studies of two ECE centers (low and high technology) involving 11 ECE teachers were compared in order to examine similarities and differences in access to digital technologies. Similarly, teachers (n=508) in two education zones were surveyed and drawn in terms of similarities and differences in access to digital technologies. Findings indicated that ECE teachers in Kenya have limited access to digital technologies due to non-availability in ECE teaching and learning environments. To address this challenge, the study recommends Ministry of education to put emphasis on funding technology resources in early childhood settings. Furthermore, teachers in ECE should be exposed to a variety of developmentally appropriate digital technologies in order to effectively enhance teaching and learning.